THE EFFECT OF A COOPERATIVE SCRIPT IN ENHANCING THE STUDENTSâ NARRATIVE WRITING - Amrizal, Amrizal; Hamdani, Zohri (STKIP Muhammadiyah Pringsewu, 2017)
AbstractÂ The objective of this study is to find out and analyze empirically the effectsofcooperative script in enhancing the narrative writing of students The study used experimental method with a control and experimental group. The study of population was 80 students âelectrical Engineering in the second semester at Muhammadiyah Lampung University 2016/2017. The subjects of the study were taken from the seven sections randomly elected by the fishbowl technique. The data collection method used pretest and posttest while data analysis used t-tests in SPSS 16.0 The study of results showed that the mean scores in the pre-test and post-test in both control and experimental groups significantly varied. First, the treatment or the cooperativescript significantly increased the performance of the second semester students in narrative text writing, from good to very good. Second, a significant difference existed in the post-test mean scores of the control and experimental groups. The treatment increased the performance of the second semester students in narrative writing. Third, the use of a cooperativescript significantly affected the performance, particularly of the experimental group.Â Keywords: Cooperative Script, Writing Skill, Narrative Text